PERAN MUI PROVINSI SULAWESI TENGAH DALAM MENETAPKAN LABEL HALAL PADA PRODUK MAKANAN - Ahmad Syaiful; Sofyan Bachmid (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2021)
Allah's teaching requires us to always maintain the halal food that we consume; it certainly contains various purposes and benefits. This article describes the role of the Indonesian Ulema Council (MUI) of Central Sulawesi Province in establishing halal labels on food products in Palu City. This study aims at finding out about the role of MUI in setting halal labels on food products for SMEs and the legal basis for setting halal labels on food products in Palu. The results of this study shows that the existence of halal certification provides benefits for producers if their product labelled a halal label in each package and has a halal certification. The seller’s income can be increased because the consumers will trust to the product with a halal label. In fact, it is not only Muslim consumers who like to consume halal products, but also non-Muslims consumers consume a lot of halal products. The determination of halal label by MUI must go through the rules that have been applied in Law no. 33 of 2014 concerning the guarantee of halal products, it has been regulated that every product that has been circulated and traded in Indonesia, especially in Palu, must have a halal certification except for haram products.